Racismo estrutural nas carreiras jurídicas públicas gaúchas - Rech Neto, Henrique (2022)
The scope of this dissertation was to investigate the reasons why professionals with predominantly black ethnic-racial characteristics practically do not exist within typical State legal careers in Rio Grande do Sul and, due to this condition, affirm that the dominant conservative model, formed in its almost entirely by individuals of white complexion who integrate and command the most high hierarchical levels of the institutions that make up the system of Justice hinders, albeit unconsciously and invariably, the integration of other individuals of different stripes in the face of an invisible structural prejudice that hangs over the respective organizations. Of course, the reason for the problem derives for issues related to the Dignity of the Human Person, whose violation of the fundamental precept is the cause of the most diverse forms of racism, especially structural; to colonial ancestry, given the predominance of Caucasian men in spaces of power from the formation and constitution of the homeland society to the current order, as well as by the imposition of its cultural methods as a form systemic reserve of authority; and, also, due to the economic aspects and absence of public policies as vectors that create difficulties for the minority black woman to gain admission to the best science teaching schools in the world Right to protect equal participation in public selections and, consequently, enable access to noble legal careers in the service gaucho public.